African American males in high school credit recovery: a critical race theory perspective - Cisneros McGilvrey, Cynthia Ann (Kansas State University, 2012)
African American males have the second highest dropout rate in this Midwest state‘s largest public school district. Often, African American male students take an abundance of elective classes but do not complete core classes that guarantee a diploma. This study documented and analyzed the experiences of African American male students who completed or attempted to complete their high school diplomas in an alternative setting. The study is significant because it reveals the importance of how time is structured in an alternative educational setting; it discloses the pervasiveness of racism in public education, and it exposes the widespread stereotyping of African American males by teachers and other authority figures. African American male students who have attended both traditional and alternative public schools have been overlooked in previous research. Self-ethnography comprised the methodology. The intersectionality of gender, race, grades, racism, athletic involvement, law, and relationships formed a crucial paradigm of this investigation. Research findings include: (a) the major difference between traditional public and alternative schools is how time is structured, (b) African American males believe that they often are stereotyped, (c) high school athletes receive special privileges that they see later as obstacles, (d) African American males sometimes deliberately assume a pleasing demeanor toward teachers, (e) African American male students respond positively to teachers who conduct themselves with clear purpose, (f) African American males returning to school for high school credit recovery demonstrate tenacity and resist stereotypes. The cornerstone tenets of CRT—racism is the norm, interest convergence, and the need for social justice for oppressed groups—were evident in the findings of the frequency of stereotyping and treatment of African American male high school athletes. In the interest of social justice for African American male students, it is recommended that teachers are provided with the following information: (a) how to avoid consciously stereotyping; (b) that African American males make conscious efforts to be approachable; (c) how to make necessary changes involving their authority. Recommended future research for African American males includes: (a) how the construction of time in traditional public schools affects their credit acquisition; (b) communication between the counseling and athletic departments; (c) the impact of athletic involvement on academics.
Keywords: African American males; High school credit recovery; Education, General (0515)